Predicting time to exhaustion during high-intensity exercise using rating of perceived exertion - Okuno, N. M.; Soares-Caldeira, L. F.; Milanez, V. F.; Perandini, L. A. B. (Science & Sports, 2015)
Objectives: This study aimed to predict the time to exhaustion (Tlim) at different high-intensity exercises using a linear regression between 14-17 points of Borg scale and their respective time, verify the agreement and compare them to the real Tlim. Methods: Nineteen healthy male subjects undertook four constant-load exhaustive exercise bouts on cycle ergometer. These tests were performed on different days and with four different intensities. The power output imposed in each test was determined based on familiarization trials in order to induce a subjects` exhaustion between 2 and 15 min. They were also asked to report the rating of perceived exertion (RPE) during these constant-load exercise bouts. The first value was freely chosen as soon as the subject felt able to accurately report RPE levels, the number corresponding to the verbal anchor on the Borg scale, within of first minute of exercise. Thereafter, whenever they felt that the RPE was increased, the value was recorded. A linear regression was fitted plotting the 14-17 RPE range as a function of time of each test. The Tlim was estimated by extrapolation of the linear relationship to the RPE 19 (Tlim19) and 20 (Tlim20). Results: The measured Tlim values were significantly higher at the Tlim19 at 230 ± 33 W, 256 ± 33 W and 289 ± 36 W (P < 0.01). However, when compared with Tlim20, there were not significant differences in intensity (P > 0.05). Furthermore, the intraclass correlation coefficients were all strong (ICC = 0.79-0.87). The RPE at same percentages of Tlim (25, 50, 75 and 100%) during the four constant-load exercise bouts were not different (P > 0.05). Conclusion: Tlim during high-intensity exercises can be accurately predicted by the use of RPE values in the 14-17 range assuming that exhaustion occurs at RPE = 20.